(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aimed to highlight the importance of applying the responsibility accounting system and the role it plays in providing accounting information in the form of performance reports that monitor the performance of officials in the departments and departments of educational institutions. Al-Muthanna University was chosen as a sample for the research. The research started from the following question: What is the role of responsibility accounting in evaluating performance at Al-Muthanna University? The importance stems from the benefits that can be achieved from applying the responsibility accounting system in educational institution, For purpose of proving the hypothesis , a questionnaire was designed and distributed to the research sample and it paragraphs analyzed . A set of conclusions were reached, the most important of which is that the responsibility accounting system helps the administration in drawing up clear administrative policies. It is also an effective control tool that can be adopted in monitoring and evaluating performance, while the most important recommendations were the need to pay attention to the issue of applying the responsibility accounting system in educational institutions in terms of planning, control and performance evaluation.